Forestry, deforestation and biodiversity in Ghana - Benhin, J.K.; Barbier, Bruno (2000)
This study seeks to examine the causes and consequences of forest loss and therefore biodiversity loss in Ghana. It examines the driving forces behind and evaluates policy options for addressing the problem of biodiversity loss. It also makes recommendations for an optimal strategy for the sustainable use of the forest and therefore the conservation of biodiversity. Cocoa, timber and maize are very important commodities in the economy of Ghana. The Structural Adjustment Programme (SAP), introduced in 1983, aimed to increase returns from timber and cocoa. Maize production also increased as a result of high rate of population growth and the need to reduce imports to correct persistent Balance of Payments deficits. However, increases in output of major food crops over the period 1965–1995 have been attributed more to land expansion than to increases in productivity. This has implications for forest loss and biodiversity. About 20% of Ghana’s tropical high forest area, where cocoa and maize are grown, consists of forest reserves, created to serve both protective and productive functions. These reserves hold all that is left of Ghana’s forests, and although the area under reserve has remained fairly constant between 1965 and 1995, much has been degraded through illegal logging, bad logging practices and legal and illegal farming activities. Virtually all unreserved forest has been converted to farmlands and fallow areas. Successfully established plantations so far cover a very insignificant area and cannot meet the increasing demand for forest resources. Increasing loss of forest and tree species has implications for the variety of fauna in the forest, which in turn influences the mechanisms and rates of regeneration, reproduction and speciation in tropical forests.